Bengawan Solo Resto And Park Di Bojonegoro - Nugraha, Alfian Setya; , Dr. Ir. Arya Ronald; , Suryaning Setyowati, ST. MT (2016)
Bojonegoro Regency is part of East Java Province. Geographically, Bojonegoro traversed by the river Bengawan Solo and became the natural border of Central Java province. Seeing the potential for tremendous Bojonegoro, very unfortunate if public spaces and natural potential malfunction and less noticed by the government. Given these potentials it is necessary to made a point to meet the needs and natural resources. And then the Bengawan Solo Resto Park is suitable to accommodate the natural resources. Basic concepts in planning and designing the Solo Resto And Park in Bojonegoro is as a culinary and recreation. With the Bengawan Solo Resto And Park is expected to become a new landmark of the place and so that people Bojonegoro has a new container for recreation and enjoy annual events are usually held on the river bengawan solo. Additionally resto park can produce solutions to problems and develop local potential for advancement Bojonegoro.